PELECEHAN SEKSUAL TERHADAP ANAK DI MEDIA SOSIAL - Hanafiah, Early Hanafiah; Widodo, Selamat (Collegium Studiosum Journal, 2024)
Children's use of technology has a significant impact on their physical, cognitive, social and emotional development. One of the technologies that children often use is social media. While social media can provide benefits, there are also negative impacts such as bullying and harassment. Therefore, supervision from parents, educators, and authorities is essential. Technology is not all good or all bad; what matters is how its use is managed to suit children's needs and development, while considering its positive and negative impacts. This research aims to find out and analyze various countermeasures that can be taken against children who experience sexual harassment on social media in accordance with the provisions in the Child Protection Law, as well as identify forms of legal protection provided to child victims of sexual harassment in cyberspace based on applicable regulations. This analysis includes measures for prevention, handling, and recovery of victims, as well as legal implementation to ensure that children's rights are optimally protected in the midst of rampant cases of harassment in the digital realm. Data collected from primary legal materials and secondary legal materials are then analyzed qualitatively. Countermeasures against child sexual abuse on social media according to Law number 35 of 2014 and Law number 12 of 2022 involve integrated preventive and enforcement actions.